Effects of a 6‐Month, Group‐Based, Therapeutic Exercise Program for Childhood Cancer Outpatients on Motor Performance, Level of Activity, and Quality of Life. Issue 1 (16th July 2015) - Beulertz, Julia; Prokop, Aram; Rustler, Vanessa; Bloch, Wilhelm; Felsch, Moritz; Baumann, Freerk T.
Abstract : Background: Exercise interventions in pediatric oncology are feasible and safe. However, scarce data are available with regard to the effectiveness of outpatient, group‐based exercise interventions. As well, the potential role of exercise to improve motor performance has not been adequately explored despite being a meaningful outcome during childhood with important implications for physical activity behavior. No study has yet demonstrated significant changes in motor performance after an exercise intervention. Procedures: This explorative, prospective study was designed to evaluate the effects of a 6‐month, group‐based, therapeutic exercise program for a mixed childhood cancer population on motor performance, level of activity, and quality of life. After cessation of inpatient medical treatment, childhood cancer outpatients aged 4–17 years exercised once a week during a 6‐month period (IG). Comparison groups included childhood cancer outpatients receiving care as usual (CG 1 ), as well as healthy peers (matched to IG by age and gender) (CG 2 ). Results: Overall motor performance, various motor dimensions, activity in sport clubs and school sports, as well as physical and emotional well‐being were significantly reduced in the IG at baseline. Significant differences between the IG and CG 1 and/or CG 2 were identified in the change of overall motor performance, single motor dimensions, overall level of activity, and emotional well‐being from baseline to post‐intervention. Conclusions: The exercise intervention was beneficial in terms of motor performance, level of activity, and emotional well‐being. As such, this study provides support for group‐based exercise as a potential strategy to improve these outcomes after inpatient medical treatment. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.